Structural Properties of ZnO Thin Films Obtained by Chemical Bath Deposition Technique - T.O. Berestok; D.I. Kurbatov; N.M. Opanasyuk; A.D. Pogrebnjak; O.P. Manzhos; S.M. Danilchenko (Журнал нано- та електронної фізики)
Zinc oxide thin films have been deposited onto glass substrates from zinc sulfate, ammonia and thiourea aqueous solution by chemical bath deposition. In the work there were specified solution preparation procedure and optimized the composition of the solution and content of component in it. X-ray diffraction and high-resolution scanning electron microscopy were used to characterize structure formation of obtaining ZnO films. As a result of investigation the effect of time deposition on the structural and substructural properties such as lattice parameters, texture quality, coherent scattering domain size was determined.